2004
DOI: 10.1530/rep.1.00080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parity and body condition at parturition on endocrine and reproductive parameters of the cow

Abstract: The effect of parity (multiparous vs primiparous) and body condition score (BCS; <3.0 or $ 3.0, lean vs fat) at parturition on metabolic and endocrine profiles from 1 month before to 2 months after parturition were studied in 42 Holstein cows grazing on improved pastures. BCS and milk production were determined every 2 weeks. Non-esterified fatty acids (NEFA), b-hydroxybutyrate (BHB), insulin, IGF-I, leptin, thyroxine (T4) and 3,3 0 ,5-tri-iodothyroinine (T3) were determined in plasma every 10 days. Progestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
160
6
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(225 citation statements)
references
References 43 publications
44
160
6
6
Order By: Relevance
“…In beef cows with low BCS (BCS ⩽ 4: scale 1 to 9) the relationship between serum leptin concentrations (2.5-3.4 ng/ml) and reproductive function is not resolvable Konigsson et al, 2008;Guzmán et al, 2012). Furthermore, similar to what was observed for the control cows in this study, in lean dairy cows (BCS ⩽ 3: scale 1 to 5) the increase in BCS did not correlate with changes with leptin concentrations (Meikle et al, 2004). Together these data provide evidence that in cows with low body fat, due to low BCS or β-adrenergic receptor agonist treatment, serum concentrations of leptin are below a putative threshold of action and may not participate in the mechanisms which function to facilitate reproductive function.…”
Section: Discussionsupporting
confidence: 53%
“…In beef cows with low BCS (BCS ⩽ 4: scale 1 to 9) the relationship between serum leptin concentrations (2.5-3.4 ng/ml) and reproductive function is not resolvable Konigsson et al, 2008;Guzmán et al, 2012). Furthermore, similar to what was observed for the control cows in this study, in lean dairy cows (BCS ⩽ 3: scale 1 to 5) the increase in BCS did not correlate with changes with leptin concentrations (Meikle et al, 2004). Together these data provide evidence that in cows with low body fat, due to low BCS or β-adrenergic receptor agonist treatment, serum concentrations of leptin are below a putative threshold of action and may not participate in the mechanisms which function to facilitate reproductive function.…”
Section: Discussionsupporting
confidence: 53%
“…This difference in the pattern of plasma insulin between primiparous and multiparous goats around parturition represents the striking result obtained in the present study. In dairy cows, plasma insulin levels start to decrease before parturition and the lowest concentrations are found at calving and then they rise soon after and are fully recovered 30 d postpartum, without differences between primiparous and multiparous subjects (Meikle et al, 2004). Adrien et al (2012) also reported a decrease in plasma insulin concentration at calving in both primiparous and multiparous dairy cows and considered this decrease as a metabolic adaptation to cope with the energy demands of lactation.…”
Section: Plasma Insulinmentioning
confidence: 98%
“…Higher leutinizing harmone (LH) pulse frequencies have also been reported in fatter cows (score 2.95 relative to score 2.35; Wright et al, 1990). Meikle et al (2004) observed that lean dairy heifers (score 2.3) also took longer to resume cyclicity than fatter heifers (score 3.3) even though the lean heifers had lower body mobilisation in early lactation. However, this effect was not observed in multiparous cows.…”
mentioning
confidence: 89%